PENGARUH PERBANDINGAN TERIGU DAN TEPUNG KELADI TERHADAP KARAKTERSTIK MIE BASAH - Rizal, Aditya Degita; Putra, I Nengah Kencana; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2012)
This research aims to find out the effect of the comparison between wheat flour and caladium flour used in moist noodle to produce moist noodle with the best quality requirements. The research design used for this research is randomized block design with comparisons between of wheat flour and caladium flour as follows: 100%:0%, 95%:5%, 90%:10%, 85%:15%, 80%:20%, 75%:25%, 70%:30% respectively. Treatments were repeated three times to obtain 21 units of the experiment and the data were analyzed by variance analysis. If there was any impact on the treatment of the analysis was followed by Duncan’s test. The result of the research have shown that comparison between of wheat flour and caladium flour had significant affects on water content, ash content, protein content, color, taste, texture, and overall acceptance, but have not significant effect on fat content, carbohydrate content and aroma. The best characteristics of moist noodle which made with comparison between of 80% terigu and 20% keladi flour with the following criteria : water content 59,82%, ash content 1,12%, protein content 4,66%, fat content 5,59%, carbohydrate content 25,65%, aroma (mostly like), color (like), taste (mostly like), texture (elastic), overall acceptance (mostly like).
Keywords: wheat flour, caladium flour, moist noodle